2008
DOI: 10.1108/02686900810899518
|View full text |Cite
|
Sign up to set email alerts
|

Corporate governance, transparency and performance of Malaysian companies

Abstract: The paper aims to examine the effect of good corporate governance practices on corporate transparency and performance of Malaysian listed companies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
49
1
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 195 publications
(59 citation statements)
references
References 82 publications
4
49
1
5
Order By: Relevance
“…Most Malaysian researches (Haron, Jantan, & Pheng, 2005;Abdul Wahab, How, & Verhoeven, 2007;Che Haat, Abdul Rahman, & Mahenthiran, 2008;Ponnu, 2008;Goh, Rasli, & Khan, 2014) use Anglo-American approaches to operationalise corporate governance quality. For instance, Haron et al (2005) investigated compliance with the listing requirements related to audit committees.…”
Section: Suggestion For a New Approach To Operationalising Corporate mentioning
confidence: 99%
“…Most Malaysian researches (Haron, Jantan, & Pheng, 2005;Abdul Wahab, How, & Verhoeven, 2007;Che Haat, Abdul Rahman, & Mahenthiran, 2008;Ponnu, 2008;Goh, Rasli, & Khan, 2014) use Anglo-American approaches to operationalise corporate governance quality. For instance, Haron et al (2005) investigated compliance with the listing requirements related to audit committees.…”
Section: Suggestion For a New Approach To Operationalising Corporate mentioning
confidence: 99%
“…In the first place, being transparent can lead external actors to understand the company better and potential investors to increase investments towards it. It is shown that one of the benefits of reporting and disclosure is the growth of long-term investors [125]. Furthermore, opportunities for cooperation with stakeholders can rise.…”
Section: Transparencymentioning
confidence: 99%
“…Corporate governance mechanisms assure donors that HL will cover enough area through their funds. In the absence of any proper governance system or if it does not properly function, the donors will not provide funds to the organization [27]. Corporate governance is important for enhancing the trust of stakeholders as supported by agency theory [50].…”
Section: Corporate Governancementioning
confidence: 99%